Thin three-layer co-extrusion lithium ion battery diaphragm, preparation method and application

By adopting a thin three-layer co-extruded lithium-ion battery separator, using a laminated structure and modifier of polypropylene and polyethylene materials, the problem of insufficient longitudinal tensile strength of the existing battery separator is solved, and a high-strength, low-thickness and high-safe separator is achieved.

CN119852647AInactive Publication Date: 2025-04-18康辉南通新材料科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510322104.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing battery separators have limitations in longitudinal tensile strength and are difficult to meet the strict requirements of high-performance batteries.

Method used

A thin three-layer coextruded lithium-ion battery separator is used, including the first surface layer, the intermediate interlayer and the second surface layer, using polypropylene and polyethylene materials respectively, and is prepared by a three-layer coextrusion die head and an online annealing process that is composited in the mold. Modifiers such as TiO2 nanoparticles and silane coupling agent are added to the intermediate interlayer.

Benefits of technology

The longitudinal tensile strength is achieved above 2200kgf/cm2, which improves the strength and durability of the diaphragm, reduces the thickness of the diaphragm, and ensures the safety and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852647A_ABST
    Figure CN119852647A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion battery diaphragms, in particular to a thin three-layer co-extrusion lithium ion battery diaphragm. The diaphragm is formed by sequentially stacking a first surface layer, a middle interlayer and a second surface layer. The longitudinal tensile strength of the thin polypropylene battery diaphragm reaches more than 2200kgf / cm < 2 > and is far higher than that of the traditional thin polypropylene battery diaphragm. Due to the characteristic, the diaphragm can bear large longitudinal tension in winding or lamination operation in the battery manufacturing process and in the battery using process, the diaphragm is effectively prevented from being broken or deformed, the diaphragm thickness is reduced to the level of 10 microns while the strength of the diaphragm is ensured, the energy density of the battery can be improved, and the safety can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium battery separators, in particular to a thin three-layer co-extruded lithium ion battery separator, and also to a preparation method and application thereof. Background Art

[0002] With the continuous development of battery technology, especially in the context of high-performance batteries such as lithium-ion batteries being widely used in electric vehicles, portable electronic devices and other fields, the requirements for the performance of battery separators are increasing. Battery separators play a key role in isolating the positive and negative electrodes and allowing ions to pass through the battery. Their tensile strength, especially the longitudinal tensile strength, directly affects the safety, stability and service life of the battery. In the manufacturing process of the battery, such as winding or lamination processes, as well as in the case of internal stress and external impact to the battery during use, the separator is required to have a sufficiently high longitudinal tensile strength to prevent rupture or deformation, and to avoid serious problems such as short circuits caused by contact between the positive and negative electrodes. However, existing battery separators have certain limitations in longitudinal tensile strength, and it is difficult to meet the strict requirements of high-performance batteries. Summary of the invention

[0003] 1. Technical issues to be resolved The technical problem to be solved by the present invention is that the existing battery separators have certain limitations in longitudinal tensile strength and are difficult to meet the strict requirements of high-performance batteries.

[0004] (II) Technical solution In order to solve the above technical problems, the present invention provides a thin three-layer co-extruded lithium-ion battery separator, which has a first surface layer, an intermediate layer, and a second surface layer. The first surface layer, the intermediate layer, and the second surface layer are stacked in sequence, the first surface layer and the second surface layer are made of polypropylene material, and the intermediate layer is made of polyethylene material.

[0005] As a preferred embodiment of the present invention, the thickness of the lithium ion battery separator is 10 to 20 μm; Wherein, the thickness of the first surface layer is 2-5 μm, the thickness of the second surface layer is 2-5 μm, and the thickness of the intermediate layer is 4-10 μm.

[0006] As a preferred embodiment of the present invention, the melt index of the polypropylene material used in the first surface layer is 0.6g / 10min~2.6g / 10min, the melt index of the polypropylene material used in the second surface layer is 0.6g / 10min~2.6g / 10min, and the melt indexes of the polypropylene materials used in the first surface layer and the second surface layer are the same or different.

[0007] As a preferred embodiment of the present invention, the melt index of the polyethylene material used in the middle interlayer is 0.3 g / 10 min to 0.8 g / 10 min.

[0008] As a preferred embodiment of the present invention, a modifier is added to the polyethylene material of the intermediate interlayer, and the modifier is TiO 2 Nanoparticles, the amount of the modifier added is 0.5% to 1.5% of the weight of the polyethylene.

[0009] As a preferred embodiment of the present invention, a silane coupling agent is added to the polyethylene material of the intermediate interlayer, and the added amount of the silane coupling agent is 0.5% to 1% of the mass of the polyethylene.

[0010] As a preferred embodiment of the present invention, the silane coupling agent is selected from one or both of γ-methacryloxypropyltrimethoxysilane and 3-aminopropyltriethoxysilane.

[0011] The present invention also provides a method for preparing a thin three-layer co-extruded lithium-ion battery separator, comprising the steps of: S1. Melting and plasticizing the materials for preparing the first surface layer, the second surface layer, and the intermediate layer to obtain melt-plasticized raw materials for preparing each layer; S2. The three-layer co-extrusion die head of the mold composite is used to prepare the molten plasticized raw materials of each layer by casting and extruding from the die head, and the film is stretched by traction to obtain a three-layer co-extruded cast film; S3. Using an online annealing process, annealing and stretching treatment; S4. After that, heat setting is performed and cooling is performed to obtain a thin three-layer co-extruded lithium-ion battery separator.

[0012] As a preferred embodiment of the present invention, in step S4, the heat setting temperature is 120-128°C, and the cooling temperature is 45-70°C.

[0013] As a preferred embodiment of the present invention, in step S1, the extruder process parameters of the first surface layer polypropylene are: the conveying section temperature is 175-185°C, the compression section temperature is 190-220°C, the melting section temperature is 210-235°C, and the screw speed is 30-70rpm; The extruder process parameters of the second surface layer polypropylene are: the conveying section temperature is 175-185°C, the compression section temperature is 190-220°C, the melting section temperature is 210-235°C, and the screw speed is 30-70rpm; The process parameters of the extruder for the intermediate interlayer polyethylene are as follows: the temperature of the conveying section is 175-185° C., the temperature of the compression section is 190-220° C., the temperature of the melting section is 210-235° C., and the screw speed is 30-80 rpm.

[0014] The present invention also provides a lithium battery, comprising the thin three-layer co-extruded lithium-ion battery separator provided by the present invention.

[0015] (III) Beneficial effects The technical solution of the present invention has the following advantages: 1. The longitudinal tensile strength of the present invention reaches 2200kgf / cm 2 This feature enables the separator to withstand greater longitudinal tension during winding or lamination operations in the battery manufacturing process and during battery use, effectively preventing the separator from rupturing or deforming, while ensuring the strength of the separator and reducing the thickness of the separator to 10μm, which can both increase the energy density of the battery and ensure safety.

[0016] 2. The present invention adopts a blending modification method to blend titanium dioxide and high-strength low melt index polyethylene in a specific ratio, so that the crystallinity and strength of the diaphragm can be taken into account; at the same time, the three-layer co-extrusion die head with in-mold compounding can avoid the cross-flow problem between the three layers of raw materials in the traditional die head production process, and also allow the three layers of the film to use different formulas of raw materials, interlayer ratios, and processing technology, so that performance and processability are taken into account. The product thickness can be reduced to about 10um, and the MD tensile strength can be increased by about 10-20%, reaching 2200kgf / cm 2 And above, the puncture strength can still be maintained above 250gf.

[0017] 3. The present invention uses an online annealing process, combining annealing and stretching processes, which significantly reduces the residence time of the diaphragm at high temperature, reduces the aging degradation of the diaphragm caused by the traditional annealing process and can improve the pore consistency of the manufactured diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the lithium ion battery separator of the present invention.

[0019] In the figure: 1-first surface layer; 2-middle layer; 3-second surface layer. DETAILED DESCRIPTION

[0020] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Example

[0021] This embodiment provides a thin three-layer co-extruded lithium-ion battery separator, the structural schematic diagram of which is shown in Figure 1 , including a first surface layer 1, an intermediate layer 2, and a second surface layer 3; the first surface layer, the intermediate layer, and the second surface layer are stacked in sequence, the first surface layer and the second surface layer are made of polypropylene material, and the intermediate layer is made of polyethylene material.

[0022] The thickness of the lithium-ion battery separator is 10 μm, wherein the thickness of the first surface layer is 3 μm, the thickness of the second surface layer is 3 μm, and the thickness of the middle interlayer is 4 μm.

[0023] The melting index of the polypropylene material used in the first surface layer is 0.8g / 10min, the mass fraction is 30%, and the melting temperature is 230℃; the melting index of the polypropylene material used in the second surface layer is 0.8g / 10min, the mass fraction is 30%, and the melting temperature is 230℃; the melting index of the polyethylene material used in the middle layer is 0.35g / 10min, the mass fraction is 38.5%, and the melting temperature is 230℃.

[0024] The polyethylene material of the middle interlayer is added with a modifier and a silane coupling agent, and the modifier is TiO 2 Nanoparticles, the amount of the modifier added is 1% of the weight of polyethylene, the silane coupling agent is 3-aminopropyltriethoxysilane (KH550), and the amount of the silane coupling agent added is 0.5% of the weight of polyethylene.

[0025] The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: S1. The materials for preparing the first surface layer, the second surface layer, and the intermediate layer are melt-plasticized to obtain melt-plasticized raw materials for preparing each layer; S2. The three-layer co-extrusion die head of the mold composite is used to prepare the molten plasticized raw materials of each layer by casting and extruding from the die head, and the film is stretched by traction to obtain a three-layer co-extruded cast film; S3. Using an online annealing process, annealing and stretching treatment; S4. After that, heat setting is performed and cooling is performed to obtain a thin three-layer co-extruded lithium-ion battery separator.

[0026] In step S1, the extruder temperature of the first surface layer and the second surface layer is 200±10°C, and the screw speed is 48rpm; the extruder temperature of the middle interlayer is set to 200±10°C, and the screw speed is 32rpm.

[0027] In step S3, the cold drawing temperature is 25°C, the stretching speed ratio is 1.28, the hot drawing temperature is 124°C, and the stretching speed ratio is 2.10.

[0028] In step S4, the heat setting temperature is 127°C and the cooling temperature is 50°C. Example

[0029] This embodiment provides a thin three-layer co-extruded lithium-ion battery separator, the structural schematic diagram of which is shown in Figure 1 , including a first surface layer 1, an intermediate layer 2, and a second surface layer 3; the first surface layer, the intermediate layer, and the second surface layer are stacked in sequence, the first surface layer and the second surface layer are made of polypropylene material, and the intermediate layer is made of polyethylene material.

[0030] The thickness of the lithium-ion battery separator is 10 μm, wherein the thickness of the first surface layer is 2 μm, the thickness of the second surface layer is 2 μm, and the thickness of the middle interlayer is 6 μm.

[0031] The melting index of the polypropylene material used in the first surface layer is 0.8g / 10min, the mass fraction is 20%, and the melting temperature is 230℃; the melting index of the polypropylene material used in the second surface layer is 0.8g / 10min, the mass fraction is 20%, and the melting temperature is 230℃; the melting index of the polyethylene material used in the middle layer is 0.55g / 10min, the mass fraction is 58.5%, and the melting temperature is 230℃.

[0032] The polyethylene material of the middle interlayer is added with a modifier and a silane coupling agent, and the modifier is TiO 2 Nanoparticles, the amount of the modifier added is 1% of the weight of polyethylene, the silane coupling agent is 3-aminopropyltriethoxysilane (KH550), and the amount of the silane coupling agent added is 0.5% of the weight of polyethylene.

[0033] The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: S1. The materials for preparing the first surface layer, the second surface layer, and the intermediate layer are melt-plasticized to obtain melt-plasticized raw materials for preparing each layer; S2. The three-layer co-extrusion die head of the mold composite is used to prepare the molten plasticized raw materials of each layer by casting and extruding from the die head, and the film is stretched by traction to obtain a three-layer co-extruded cast film; S3. Using an online annealing process, annealing and stretching treatment; S4. After that, heat setting is performed and cooling is performed to obtain a thin three-layer co-extruded lithium-ion battery separator.

[0034] In step S1, the extruder temperature of the first surface layer and the second surface layer is 210±10°C, and the screw speed is 32rpm; the extruder temperature of the middle interlayer is set to 200±10°C, and the screw speed is 48rpm.

[0035] In step S3, the cold drawing temperature is 28°C, the stretching speed ratio is 1.22, the hot drawing temperature is 125°C, and the stretching speed ratio is 2.15.

[0036] In step S4, the heat setting temperature is 127°C and the cooling temperature is 50°C. Example

[0037] This embodiment provides a thin three-layer co-extruded lithium-ion battery separator, the structural schematic diagram of which is shown in Figure 1 , including a first surface layer 1, an intermediate layer 2, and a second surface layer 3; the first surface layer, the intermediate layer, and the second surface layer are stacked in sequence, the first surface layer and the second surface layer are made of polypropylene material, and the intermediate layer is made of polyethylene material.

[0038] The thickness of the lithium-ion battery separator is 10 μm, wherein the thickness of the first surface layer is 3 μm, the thickness of the second surface layer is 3 μm, and the thickness of the middle interlayer is 4 μm.

[0039] The melting index of the polypropylene material used in the first surface layer is 0.8g / 10min, the mass fraction is 30%, and the melting temperature is 230℃; the melting index of the polypropylene material used in the second surface layer is 0.7g / 10min, the mass fraction is 30%, and the melting temperature is 230℃; the melting index of the polyethylene material used in the middle layer is 0.35g / 10min, the mass fraction is 38.5%, and the melting temperature is 230℃.

[0040] The polyethylene material of the middle interlayer is added with a modifier and a silane coupling agent, and the modifier is TiO 2 Nanoparticles, the amount of the modifier added is 0.5% of the weight of polyethylene, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane (KH570), and the amount of the silane coupling agent added is 1% of the weight of polyethylene.

[0041] The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: S1. The materials for preparing the first surface layer, the second surface layer, and the intermediate layer are melt-plasticized to obtain melt-plasticized raw materials for preparing each layer; S2. The three-layer co-extrusion die head of the mold composite is used to prepare the molten plasticized raw materials of each layer by casting and extruding from the die head, and the film is stretched by traction to obtain a three-layer co-extruded cast film; S3. Using an online annealing process, annealing and stretching treatment; S4. After that, heat setting is performed and cooling is performed to obtain a thin three-layer co-extruded lithium-ion battery separator.

[0042] In step S1, the extruder temperature of the first surface layer and the second surface layer is 210±10°C, and the screw speed is 48rpm; the extruder temperature of the middle layer is set to 200±10°C, and the screw speed is 32rpm.

[0043] In step S3, the cold drawing temperature is 26°C, the stretching speed ratio is 1.24, the hot drawing temperature is 125°C, and the stretching speed ratio is 2.10.

[0044] In step S4, the heat setting temperature is 128°C and the cooling temperature is 50°C. Example

[0045] This embodiment provides a thin three-layer co-extruded lithium-ion battery separator, the structural schematic diagram of which is shown in Figure 1 , including a first surface layer 1, an intermediate layer 2, and a second surface layer 3; the first surface layer, the intermediate layer, and the second surface layer are stacked in sequence, the first surface layer and the second surface layer are made of polypropylene material, and the intermediate layer is made of polyethylene material.

[0046] The thickness of the lithium-ion battery separator is 20 μm, wherein the thickness of the first surface layer is 5 μm, the thickness of the second surface layer is 5 μm, and the thickness of the middle interlayer is 10 μm.

[0047] The melting index of the polypropylene material used in the first surface layer is 2.0g / 10min, the mass fraction is 25%, and the melting temperature is 230℃; the melting index of the polypropylene material used in the second surface layer is 2.0g / 10min, the mass fraction is 25%, and the melting temperature is 230℃; the melting index of the polyethylene material used in the middle layer is 0.55g / 10min, the mass fraction is 48.5%, and the melting temperature is 230℃.

[0048] The polyethylene material of the middle interlayer is added with a modifier and a silane coupling agent, and the modifier is TiO 2 Nanoparticles, the amount of the modifier added is 1% of the weight of polyethylene, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane (KH570), and the amount of the silane coupling agent added is 0.5% of the weight of polyethylene.

[0049] The method for preparing the lithium ion battery separator provided in this embodiment comprises the following steps: S1. The materials for preparing the first surface layer, the second surface layer, and the intermediate layer are melt-plasticized to obtain melt-plasticized raw materials for preparing each layer; S2. The three-layer co-extrusion die head of the mold composite is used to prepare the molten plasticized raw materials of each layer by casting and extruding from the die head, and the film is stretched by traction to obtain a three-layer co-extruded cast film; S3. Using an online annealing process, annealing and stretching treatment; S4. After that, heat setting is performed and cooling is performed to obtain a thin three-layer co-extruded lithium-ion battery separator.

[0050] In step S1, the extruder temperature of the first surface layer and the second surface layer is 210±10°C, and the screw speed is 80rpm; the extruder temperature of the middle layer is set to 200±10°C, and the screw speed is 80rpm.

[0051] In step S3, the cold drawing temperature is 30°C, the stretching speed ratio is 1.22, the hot drawing temperature is 124°C, and the stretching speed ratio is 2.18.

[0052] In step S4, the heat setting temperature is 128°C and the cooling temperature is 50°C.

[0053] Comparative Example 1 This comparative example provides a single-layer polypropylene lithium-ion battery separator.

[0054] The thickness of the lithium-ion battery separator is 10 μm. Two types of polypropylene materials are used, namely, polypropylene with a melt index of 2.0 g / 10 min, a mass fraction of 50%, and a melting temperature of 230°C, and polypropylene with a melt index of 0.8 g / 10 min, a mass fraction of 50%, and a melting temperature of 230°C. The two types of polypropylene are melt-extruded separately.

[0055] The preparation method of the lithium ion battery separator provided in this comparative example comprises: two raw materials are extruded by two extruders respectively, the extruder temperature is 210±10°C, and the screw speed is 52rpm; cast extrusion, cold drawing, hot drawing, and heat setting to form a single-layer PP lithium ion battery separator with a thickness of 10μm. The cold drawing temperature is 26°C, the stretching speed ratio is 1.20, the hot drawing temperature is 125°C, the stretching speed ratio is 2.20, and the heat setting temperature is 128°C.

[0056] The performance tests of the diaphragms obtained in the examples and comparative examples were carried out, including tensile strength, puncture strength, and closed-cell rupture temperature tests.

[0057] The test methods for tensile strength and puncture strength are GB / T36363-2018, and the closed-cell membrane rupture temperature test is thermomechanical analysis.

[0058] The test data is shown in Table 1 below.

[0059] Table 1 Performance data of Examples 1 to 4 and Comparative Example 1 It can be seen from Table 1 that the longitudinal tensile strength of the diaphragm obtained in the embodiment of the present invention can reach 2200kgf / cm 2The above is much higher than the traditional thin polypropylene battery separator in the comparative example. The puncture strength of the separator obtained in the embodiment of the present invention is also significantly better than that of the comparative separator, and the closed-cell temperature is significantly lower than that of the comparative separator. These characteristics enable the separator to withstand large longitudinal tension during winding or lamination operations in the battery manufacturing process and during battery use, effectively preventing the separator from rupturing or deforming, and reducing the separator thickness to 10μm while ensuring the strength of the separator, which can both improve the energy density of the battery and ensure safety.

[0060] It should be clear that the various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. For the embodiments of the method, the relevant parts can refer to the partial description of the device embodiment (adopted according to the writing situation). The present invention is not limited to the specific structure described above and shown in the figure. In addition, for the sake of brevity, the detailed description of the known method technology is omitted here.

[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A thin three-layer co-extruded lithium-ion battery separator, characterized in that: The diaphragm comprises a first surface layer, an intermediate layer and a second surface layer. The first surface layer, the intermediate layer and the second surface layer are stacked in sequence. The first surface layer and the second surface layer are made of polypropylene material, and the intermediate layer is made of polyethylene material.

2. The lithium ion battery separator according to claim 1, characterized in that The thickness of the lithium ion battery separator is 10 to 20 μm; Wherein, the thickness of the first surface layer is 2-5 μm, the thickness of the second surface layer is 2-5 μm, and the thickness of the intermediate layer is 4-10 μm.

3. The lithium ion battery separator according to claim 1, characterized in that The melting index of the polypropylene material used in the first surface layer is 0.6g / 10min~2.6g / 10min, and the melting index of the polypropylene material used in the second surface layer is 0.6g / 10min~2.6g / 10min. The melting indexes of the polypropylene materials used in the first surface layer and the second surface layer are the same or different.

4. The lithium ion battery separator according to claim 1, characterized in that The melt index of the polyethylene material used in the middle interlayer is 0.3 g / 10 min to 0.8 g / 10 min.

5. The lithium ion battery separator according to claim 1, characterized in that A modifier is added to the polyethylene material of the middle interlayer, wherein the modifier is TiO2 nanoparticles, and the amount of the modifier added is 0.5% to 1.5% of the weight of the polyethylene.

6. The lithium ion battery separator according to claim 1 or 5, characterized in that: A silane coupling agent is added to the polyethylene material of the middle interlayer, and the added amount of the silane coupling agent is 0.5% to 1% of the weight of the polyethylene.

7. The lithium ion battery separator according to claim 6, characterized in that The silane coupling agent is selected from one or both of γ-methacryloxypropyltrimethoxysilane and 3-aminopropyltriethoxysilane.

8. A method for preparing a thin three-layer co-extruded lithium-ion battery separator according to any one of claims 1 to 7, characterized in that: Includes steps: S1. Melting and plasticizing the materials for preparing the first surface layer, the second surface layer, and the intermediate layer, respectively, to obtain melt-plasticized raw materials for preparing each layer; S2. The three-layer co-extrusion die head of the mold composite is used to prepare the molten plasticized raw materials of each layer by casting and extruding from the die head, and the film is stretched by traction to obtain a three-layer co-extruded cast film; S3. Using an online annealing process, annealing and stretching treatment; S4. After that, heat setting is performed and cooling is performed to obtain a thin three-layer co-extruded lithium-ion battery separator.

9. The preparation method according to claim 8, characterized in that: In step S4, the heat setting temperature is 120-128°C, and the cooling temperature is 45-70°C.

10. A lithium battery, characterized in that: A thin three-layer co-extruded lithium-ion battery separator comprising any one of claims 1 to 7.

Citation Information

Patent Citations

  • Polyolefin multi-layer porous diaphragm for lithium ion battery and preparation method thereof

    CN102064299A

  • Polypropylene / polyethylene / polypropylene three-layer co-extruded lithium-ion battery separator and preparation method thereof

    CN107331822A

  • Multilayer micro-porous polyolefin diaphragm and production method thereof

    CN107808943A

  • Preparation method of high-wettability polyolefin diaphragm for lithium ion battery

    CN115084776A